Pengaruh Pemberian Video Edukatif Pendidikan Pra Nikah Terhadap Pengetahuan Remaja Pada Pendidikan Pranikah Di Wilayah Kerja Puskesmas Pulo Lor - Bherty, Chanda Paramitha; Mudhawaroh, Mudhawaroh; Fitrah Ningtyas, Septi; Candra Permana, Arief (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2025)
Marriages entered into by minors (those under the age of nineteen) are considered early marriages.  Child marriage is influenced by several elements, such as economics, culture, parents' and guardians' roles, and educational opportunities in both formal and non-formal settings.  Approaches to Research  This study used a one-group pre- and post-test design to conduct quantitative research utilizing the pre-experimental approach.  It is a cross-sectional time study.  Nineteen people filled out the survey, and the Incidental Sampling method was used to determine the sample.  Two-Sample Test  The colmogorof smirnof test was used to check for normality before the bivariate test was conducted.  After making sure the data was normal, a dependent t-test was used.  The test findings indicate a Sig (2-Tailed) value less than 0.05, with a 0.000 value, according to the results of the conducted test.  Findings suggest a correlation between teenage monitoring in Pulo Lor village, Jombang District, Jombang Regency, and the distribution of instructional films for premarital education.